HUBUNGAN FAKTOR LINGKUNGAN DAN RIWAYAT DIARE DENGAN STATUS GIZI PENDEK PADA ANAK BALITA USIA 6-59 BULAN DI KAWASAN TIMUR PROVINSI PRIORITAS PENANGANAN STUNTING INDONESIA - Adhi, Kadek Tresna; Suwandewi, Ni Made Aryati (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 1 (2024): April 2024DO - 10.24843/ACH.2024.v11.i01.p12, 2024)
Stunting is a condition when a child experiences growth disturbance in height according to his age. This study aims to analyze the relationship between environmental factors and a history of diarrhea with short nutritional status in children aged 6-59 months in the eastern region of Indonesia's priority stunting management province. This research was conducted with a cross-sectional design using secondary data from SSGI 2021 data. The sample for this study was 9,124 children aged 6-59 months. Data were analyzed descriptively and bivariately using chi-square analysis. The study found that having a latrine (p<0.001; OR=1.56; 95% CI=1.39-1.73) is associated with the occurrence of stunting in children under five. With this, it is necessary to carry out education on Clean and Healthy Behavior (PHBS) and increase environmental cleanliness. Keywords: Stunting, history of diarrhea, sources of drinking water, ownership of latrines